Overnight staffing in Canadian neonatal and pediatric intensive care units - Maratta, Christina; Hutchison, Kristen; Nicoll, Jessica; Bagshaw, Sean M.; Granton, John; Kirpalani, Haresh; Stelfox, Henry Thomas; Ferguson, Niall; Cook, Deborah; Parshuram, Christopher S.; Moore, Gregory P. (Frontiers in Pediatrics, 2023)
conceptualized and designed the study, interpreted data and results, reviewed and revised the manuscript. Kristen Hutchison conceptualized the study, designed the collection instrument, coordinated and carried out data collection, interpreted data and reviewed the manuscript. Dr Maratta conceptualized the study, carried out the data analyses, interpreted data and results, drafted the initial manuscript and revised the final manuscript. Dr Nicoll interpreted data and results, reviewed and revised the manuscript. Dr Parshuram and Dr Moore conceptualized and designed the study, designed the data collection instruments, coordinated and supervised data collection, carried out the data analyses, interpreted data and results and reviewed and revised the manuscript.